SUCCESSFUL CASES OF INTERNATIONAL COMPANIES IN A FIELD OF CORPORATE SOCIAL RESPONSIBILITY - Dluhopolska, Tetiana; Sentyk , Maksym (Socio-economic relations in the digital society, 2022)
The purpose of the study is to generalize the best practices of corporate social responsibility of international companies, especially under the influence of the global pandemic of COVID-19. The research used methods of logical generalization, analysis, comparison, grouping, graphic and tabular. A feature of corporate social responsibility is its affiliation to a public or quasi-public good that combines corporate governance and public sector economics. Global trends indicate a direct connection between social responsibility and the reputation of companies, as its most important factor is the quality of goods and services (20.1%), management quality (14.8%), citizenship (14.4%), financial success (13.2%) and innovation (13.1%).The global impact of the COVID-19 pandemic contributed to the fact that organizations in an accelerated mode began to develop their own strategic flexibility and various models of corporate social responsibility. Therefore, in 2022, the rating of socially responsible companies was led by: Rolex, Ferrari, Lego Group, Rolls-Royce, Mercedes-Benz, Har-ley-Davidson, The Bosch Group, PayPal, Netflix, and Intel. The COVID-19 pandemic has contributed to the emergence of new social initiatives: from the creation of an innovative fund for climate solutions to abandoning the use of plastic, to providing children from low-income families with free access to the Internet and gadgets. The growth of consumer loyalty and the increase in the reputation of corporations as attractive employers directly affect the increase in sales volumes, the motivation of employees, the desire of the state and society to interact with socially responsible companies, and the growth of the market value of companies.
Keywords: business; corporate social responsibility; economical, ecological and social duties; mechanism of business’ social responsibility; nonfinancial report; corporation